Corruption and Public Pension Underfunding - Liu, Cheol; John L. Mikesell; Tima T. Moldogaziev (KDI School of Public Policy and Management, 2020)
Corruption exacerbates state pension underfunding through all relevant aspects: a more generous pension benefit promise, lower actuarially required contributions (ARC), lower actual contributions, and poorer investment performance. By reducing corruption by one standard deviation from the mean, states could have annually saved pension benefit by 10.24% (or, $1,894.64 per recipient), increased ARC by 4.40%, elevated actual contribution by 8.46%, and improved investment return by 4.72%, in the period 2003-2013, compared to those at the mean of corruption. Improved insulation of pension operations from corrupt officials, as well as reduction of public corruption, can make a significant contribution to reducing the pension funding crisis that haunts American state and local government.